Hypertensive retinopathy and the risk of hemorrhagic stroke - A/L Thiagarajah, Ramani (2018)
Background Hemorrhagic stroke and hypertensive retinopathy are known end organ damage, with hemorrhagic stroke having deleterious consequence to the patients. This study is to correlate between hypertensive retinopathy and hemorrhagic stroke. Methods All patients with with hypertension with and without hemorrhagic stroke were recruited. Funduscopic examination was performed and then graded based on Wong and Mitchell hypertensive retinopathy classification. Clinical and radiological parameter included are demography, vital signs, Glasgow Coma Scale(GCS) on admission, clot volume, site of clot, Intra-Cerebral Hemorrhage (ICH) score and Glasgow Outcome Scale (GOS) score. Data were collected and correlated with the severity of hypertensive retinopathy. Results Fifty hypertensive patient without hemorrhagic stroke and fifty one patients with hemorrhagic stroke were recruited. In the hemorrhagic stroke group, 21 had low severity (normal/mild retinopathy changes) accounting for 41.2% and 30 patients had high severity (moderate and severe retinopathy). In the non hemorrhagic stroke patients 49 had low severity and 1 had high severity (p value 0.001). Low severity showed better GCS score on admission as compared to high severity, (p value of 0.003). Low severity also showed a clot volume less than 30ml, (p value 0.001) and also statistically significant with an ICH score of between 0-2 in most of the patients, (p value 0.006). Lastly, we compared the GOS score of patients and found a favourable outcome of GOS score 4-5 in low severity retinopathy for 17 patients with only 4 having unfavourable outcome (GOS score 1-3). As for high severity, 23 patients hadunfavourable outcome with 7 having favourable outcome, this was statistically significant, (p value of 0.001). Conclusion Low severity retinopathy were found to have small clot volume and most likely treated by medical management and better outcome. With high severity retinopathy had larger clot volume and requiring surgical intervention and poorer outcome.